Assessing The Investment Climate In The Maghreb Countries - Mecibah, Ahmed (University of Eloued جامعة الوادي, 2025)
This study examines the investment climate, its components, and key international indicators used to assess it, such as those from UNCTAD, the World Bank, the Heritage Foundation, the World Economic Forum, and Transparency International. The findings show that Maghreb countries hold modest positions in global rankings, indicating limited progress in improving their investment environments. The study calls for stronger reforms, competitive incentives, and facilitative measures to make these countries more attractive to foreign direct investment.
مقال
Keywords: Investment climate; foreign direct investment; indicators; Maghreb countries.